Analysis of Enterprise Risk Management Maturity Level at PT. XYZ - Muhamad Rifnaldy Pratama; Dominicus Savio Priyarsono; Siti Jahroh (Green Publisher Indonesia, 2026)
This research aims to evaluate the maturity level of the implementation of Enterprise Risk Management (ERM) at PT. XYZ through a maturity assessment process based on the Technical Guidelines for the Assessment of the Risk Maturity Index (RMI) issued by the Ministry of SOEs, namely Number SK-8/DKU.MBU/12/2023 and PER-2/MBU/03/2023. The research background is based on the increasing complexity of global risks and regulatory demands, which require companies to implement risk management effectively. This study uses a combination of primary and secondary data collected through questionnaires, in-depth interviews, and analysis of company documents. Data analysis was carried out descriptively using a scoring system, as well as SWOT and PESTEL analyses to formulate improvement strategies. The results of the study are expected to illustrate the actual conditions of ERM implementation at PT. XYZ, measure its maturity level based on the five dimensions of the RMI, and develop the necessary follow-up strategies to strengthen the effectiveness of risk management in a sustainable manner. These findings provide practical contributions for companies in improving risk governance, as well as academic contributions by enriching the literature on the application of maturity assessments in corporate risk management.